An empirical investigation of organisational e-readiness impact on e-procurement implementation. Issue 4 (1st January 2012) - Naseebullah, L.; Basri, Shuib; Dominic, P.D.D.; Jehangir, Muhammad
Electronic procurement (e-procurement) is an application of electronic commerce (e-commerce) that facilitates the corporate purchasing over the internet. Nowadays, e-procurement is becoming one of the most widespread Information Technology (IT) solutions for industries, business and government agencies. However, successful implementation of e-procurement is uncertain among procurement executives owing to non-organisational e-readiness assessment. In this paper, a proposed framework is developed that consolidates relevant factors, which have been categorised into perceived management readiness, perceived technological readiness and perceived environmental readiness. Data was collected from 142 manufacturing industries of central Malaysia and analysed through multiple regression. The empirical results show that organisational e-readiness has a positive and significant impact on e-procurement implementation.